2019
DOI: 10.3389/fmicb.2019.01912
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Captivity and Season on the Gut Microbiota of the Brown Frog (Rana dybowskii)

Abstract: The gut microbiota of amphibians is affected by exogenous and endogenous factors. We performed a comprehensive analysis using high-throughput sequencing technology and functional predictions and observed general changes in the gut microbiota of frogs in different growth stages, seasons, and growth environments. There were no significant differences in microbial richness and diversity between juvenile and adult wild frogs, between the summer and autumn groups of captive frogs, or between wild and captive frogs.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 63 publications
3
44
0
Order By: Relevance
“…At present, the brown frog farming industry is stagnant, primarily due to the long growth cycle (at least 18 months from hatching to slaughtering), complex management procedures based on life history (primarily including spawning, hatching, tadpoles, metamorphosis, the growth of 1-year-old young frogs, hibernation, emergence, the growth of 2-year-old young frogs and other stages of feeding and management techniques), and high incidence of disease in frog farms ( Tong et al, 2019 ). Diseases that frequently occur during the growth of frogs are a considerable obstacle to the development of the brown frog aquaculture industry ( Xiang et al, 2018 ; Tong et al, 2019 ). Most diseases of captive amphibians are directly or indirectly related to feeding and management ( Densmore and Green, 2007 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…At present, the brown frog farming industry is stagnant, primarily due to the long growth cycle (at least 18 months from hatching to slaughtering), complex management procedures based on life history (primarily including spawning, hatching, tadpoles, metamorphosis, the growth of 1-year-old young frogs, hibernation, emergence, the growth of 2-year-old young frogs and other stages of feeding and management techniques), and high incidence of disease in frog farms ( Tong et al, 2019 ). Diseases that frequently occur during the growth of frogs are a considerable obstacle to the development of the brown frog aquaculture industry ( Xiang et al, 2018 ; Tong et al, 2019 ). Most diseases of captive amphibians are directly or indirectly related to feeding and management ( Densmore and Green, 2007 ).…”
Section: Discussionmentioning
confidence: 99%
“…Functional predictions can link the structure of the gut microbiome with the function of the gut microbiota and thus may better clarify the pathogenesis ( Xiong et al, 2017 ; Yu et al, 2018 ). Several studies have shown that captivity may increase the relative abundance of some potential pathogenic bacteria in the amphibian gut microbiota ( Xiang et al, 2018 ; Tong et al, 2019 ). Studies have been conducted on the correlation between disease occurrence and the composition of the gut microbiome in some aquaculture animals (e.g., shrimp) ( Xiang et al, 2018 ; Tong et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The wild populations of gut microbiota in Drosophila was shown to vary with collection location and diet (Adair et al, 2018, Wong et al, 2013, Staubach et al, 2013, Martinez-Porchas et al, 2017. In other insects and wild populations of vertebrates, gut microbiota was shown to change even with seasonality (Behar et al, 2008, Ferguson et al, 2018, Tong and Zhang, 2019, Maurice et al, 2015).…”
Section: 1mentioning
confidence: 99%